The Perceived Facilitators and Barriers of Research Production among Members of an Online Research Community of Practice - Al Amiri, Nabeel; Al Qawasmeh, Khaled; Johnson, Shimol; Alayli, Rania (Universitas Airlangga, 2025)
Introduction: Nurses, a vast portion of the healthcare workforce, have made a low contribution to achieving healthcare organizational visions and strategies in producing research. The study aimed to identify the facilitators and barriers to research production among members of a community of practice (CoP). Method: This study utilized a descriptive qualitative research design, conducting a focus group discussion. Those members were provided with education, mentorship, and support over 12 months from January 2023 to January 2024. h a convenience sample of 21 members from the targeted CoP. Results: The online CoP provided members with several opportunities to compensate for any deficit in the existing individual, social, and organizational support system. However, the study highlighted several barriers to research among the community members, including individual factors, i.e., time limitations and lack of member’s knowledge and expertise, social factors, i.e., lack of collaboration among colleagues, and organizational factors, i.e., lack of organization and unit support, resources, and workload. Conclusion: The study revealed satisfactory progress in the members' research projects and recommended extending their learning and training period. The study suggests extending the members' education and training period, including psychological preparation, and providing them with additional skills such as persuasion, negotiation, and interpersonal skills to overcome existing research barriers. Moreover, further studies are required to assess the long-term impact, for example, after one or two years of the online CoP on members' research productivity. Further research to explore the facilitators and barriers of research production among CoP members in various contexts.